2021
DOI: 10.1007/s00223-021-00864-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Microchannel Architectures Inside the Subchondral Bone in Relation to Estimated Hip Reaction Forces on the Human Femoral Head

Abstract: The interplay between articular cartilage (AC) and subchondral bone (SB) plays a pivotal role in cartilage homeostasis and functionality. As direct connective pathways between the two are poorly understood, we examined the location-dependent characteristics of the 3D microchannel network within the SB that connects the basal cartilage layer to the bone marrow (i.e. cartilage-bone marrow microchannel connectors; CMMC). 43 measuring points were defined on five human cadaveric femoral heads with no signs of osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Similarly, Wang et al reported that EVs containing miR-221-3p might attenuate OA by enhancing proliferation and migration of cartilage chondrocytes, but the exact mechanism was not further explored [27]. Considering the substantial mechanical/biochemical crosstalk between articular cartilage and subchondral bone [21,23,24], here, we studied EVs as a possible means for cell-cell communication between these tissues. In this regard, miR-221-3p was particularly interesting due to its mechanosensitive nature [16].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, Wang et al reported that EVs containing miR-221-3p might attenuate OA by enhancing proliferation and migration of cartilage chondrocytes, but the exact mechanism was not further explored [27]. Considering the substantial mechanical/biochemical crosstalk between articular cartilage and subchondral bone [21,23,24], here, we studied EVs as a possible means for cell-cell communication between these tissues. In this regard, miR-221-3p was particularly interesting due to its mechanosensitive nature [16].…”
Section: Discussionmentioning
confidence: 98%
“…Based on our results, we hypothesize that the bone formation capacity of osteoblasts is regulated by the signal of miR-221-3p, mediated by EVs derived from chondrocytes. In previous studies, our group has demonstrated the existence of microchannel structures at the interface of bone and cartilage, which can potentially be pathways for the transportation of EVs and chondrocyte-osteoblast communication [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs have been shown to mediate cell-cell communication by transferring cargos containing miRNAs, and the bilayer of EVs can protect miRNAs from RNase-induced degradation during the transportation process. Given the existence of microchannels between cartilage and bone [100,101], EVs mediated miRNAs' regulation on Wnt signaling could be a center of attraction for innovation and an important area to perform an in-depth study of cell-cell communication between the joint tissues.…”
Section: Future Perspectivementioning
confidence: 99%
“… 15 As nano-size membrane vesicles, EVs can be delivered quickly among tissues, even cross the microcrack channels and vessel channels between bone and cartilage interface, facilitating bone-cartilage communication. 16 More importantly, the lipid bilayer of EVs could protect the miRNAs from degradation during the transportation process. 17 With the intercellular communication capability, EVs have been exploited to deliver exogenous therapeutic reagents for decades.…”
Section: Introductionmentioning
confidence: 99%